Reading vers une architecture, otherwise - Diniz, V. B.; Basto, S. P.; Caldas, J. C.; Bouye, M. Z.; Kikuchi, F.; Sequeira, M. (LC. Revue de recherches sur Le Corbusier, 2025)
“Reading Vers une architecture, Otherwise”, assembles two interviews with contemporary studio professors at the school, conducted by participants in the workshop. Their conversations offer a more personal and speculative register in which the book reappears not as a stable reference, but as a productive source of friction: a document to be revisited and disputed, whose shifting place in architectural education reveals the evolving contours—and the ongoing fragility—of the modern canon.